Understanding The Importance Of Balanced Nutrition: Steps To Optimal Health - Firayani, Firayani (Journal Nutrizione, 2024)
Fulfillment of balanced nutrition is the main foundation in supporting optimal health throughout the lifespan. This article aims to explain the importance of balanced nutrition, outline practical steps towards proper nutritional consumption patterns, and explore its long-term health implications. Qualitative research methods were used in the form of in-depth interviews with 15 respondents from various age ranges and socio-economic backgrounds regarding eating habits, nutritional awareness, and barriers to implementing balanced nutrition. Key findings indicate that awareness of macronutrients and micronutrients varies widely, but strategies such as menu planning, nutrition education, and access to healthy food sources play an important role in improving the quality of daily consumption. Discussions address the role of cultural, economic, and environmental factors in dietary practices, and suggest collaborative actions between individuals, health workers, and the government. This article is expected to be a reference for public health practitioners and policy makers in designing nutrition education programs and community-based interventions.